Human Metapneumovirus Infection and Genotyping of Infants in Rural Nepal. (2nd November 2020) - Perchetti, Garrett A; Wilcox, Naomi; Chu, Helen Y; Katz, Joanne; Khatry, Subarna K; LeClerq, Steven C; Tielsch, James M; Jerome, Keith R; Englund, Janet A; Kuypers, Jane
Abstract: Background: Acute respiratory tract infections are a serious clinical burden in infants; human metapneumovirus (HMPV) is an important etiological agent. We investigated genotypic variation and molecular epidemiological patterns among infants infected with HMPV in Sarlahi, Nepal, to better characterize infection in a rural, low-resource setting. Methods: Between May 2011 and April 2014, mid-nasal swabs were collected from 3528 infants who developed respiratory symptoms during a longitudinal maternal influenza vaccine study. Sequencing glycoprotein genes permitted genotyping and analyses among subtypes. Results: HMPV was detected by reverse-transcriptase polymerase chain reaction (RT-PCR) in 187 (5%) infants, with seasonality observed during fall and winter months. Phylogenetic investigation of complete and partial coding sequences for the F and G genes, respectively, revealed that 3 genotypes were circulating: A2, B1, and B2. HMPV-B was most frequently detected with a single type predominating each season. Both HMPV genotypes exhibited comparable median viral loads. Clinically significant differences between genotypes were limited to increased cough duration and general respiratory symptoms for type B. Conclusions: In rural Nepal, multiple HMPV genotypes circulate simultaneously with an alternating predominance of a single genotype and definitive seasonality. No difference in viral load was detected by genotype and symptom severity was not correlated with RT-PCR cycle threshold or genotype. Abstract : In rural Nepal, multiple HMPV genotypes circulate simultaneously with an alternating predominance of a single genotype and definitive seasonality. No difference in viral load was detected by genotype and symptom severity was not correlatedwith RT-PCR cycle threshold or genotype.